Waterproofing - Kumar, Gaurav (AMC Indian Journal of Civil Engineering, 2025)
Waterproofing is a protective process that prevents water from penetrating structures like buildings, often using barriers, drainage systems, and chemical treatments to protect against water damage, leaks, and structural degradation. It involves a range of methods, such as applying coatings (like polyurethane or cementitious), using membranes (liquid-applied or sheet-based), and creating proper slopes and grooves for drainage. Proper waterproofing is essential to prevent issues like mold and to extend the life of a structure. The present paper discusses building proofing with acrylic cementitious polymer modified flexible coating, general waterproofing, waterproofing of water tanks, and waterproof coating.